Dialogues between the creation of comic videos on TikTok and the concept of gag in clowning (Urdimento: Revista de Estudos em Artes Cênicas, 2022)
This article aims to establish a dialogue between the process of creating comic videos on TikTok and the concept of gag in clowning, seeking to reflect on the different possibilities of building the comic effect at the intersection between the practices ​​of clowning and short videos. The study's starting point was my experience with creating videos on the platform, which made me question myself about the use of imitation, which is a common element in creating short videos, and the different versions produced through the appropriation of other jokes. Based on theoretical investigations, this research discusses the concepts of the gag, the internet meme and the comic performance to contextualize the report of three experiments carried out by the clown Hipotenusa, interpreted by me, seeking to contribute to studies on comic creation in digital media.
Keywords: Clowning; Gag; TikTok; Comic; Performance